Decency, Humility, and Obedience: Spatial Discipline in the Baptist Rehab Centre - Igor Mikeshin (Journal of Ethnology and Folkloristics)
This paper scrutinises the role of place and space in the process of Christian rehabilitation. This process is an interconnection of the rehabilitation of the addicted people and conversion to a particular kind of Christianity, working as an inseparable twofold process. The narrative of conversion in the rehabilitation ministry is impacted by the 150-year history of Russian Baptists, the rich sociocultural context of contemporary Russia, the junkie and prison context of the people in rehabs, and a very specific Russian Synodal translation of the Bible. I demonstrate the role of space in the implementation of rehab rules and discipline, Christian dogmatics, and construction of the Christian self. The organisation of space in the rehabs very much resembles prison, while also following the common dogmatic principles of the program. At the same time, rehabilitation is enforced by harsh conditions, a strict regime, and the idea of proper Christian family.